ANALISIS PENERAPAN PSAK NO 45 TERHADAP LAPORAN KEUANGAN ENTITAS NIRLABA : (Studi Kasus Pada LSM BENGKEL APPeK NTT Tahun 2016-2017) - MUNAWAR; ANDEREAS SERAN ATOK; HERNI SUNARYA (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
This research aims to find out and analysis financial statements non-governmental organizationbased Bengkel APPeK NTT PSAK No. 45. The data used in this research is the interview,observation and documentation. The research method used is qualitative and quantitative methods.Technical analysis is a descriptive qualitative nature outlines, describes and compares the datawith the existing theory.The results of this study indicate that Ngo Bengkel APPeK NTT alreadyimplement PSAK 45 about Nonprofit Entity financial reporting. But viewed from the conformityof the financial statements Bengkel APPeK NTT and PSAK 45 there are still differences in thepresentation of the financial statements. Financial report-Bengkel APPeK is Report: financialposition, activity reports (not bound, tied and bound While permanent) and cash flow statement.While PSAK 45 which include: Financial Position Reports, activity reports, cash flow statementand the notes to financial statements. The difference is also visible in the mention of the name ofaccounts in the financial statements and the Bengkel APPeK NTT also did not present the notes tofinancial statements. It is recommended that non-governmental organization Bengkel APPeK NTTpay more attention to the suitability of the financial reports made with generally acceptedstandards for nonprofit entities.